Modified Delphi expert elicitation of the clinical and economic burden of obstructive hypertrophic cardiomyopathy in England and Northern Ireland - Faizel Osman; Michael Hurst; Belinda Sandler; Taryn Krause; Carla Zema; Teresa Lemmer; Kathleen Noon; Deepak Alexander (BMJ Open)
Objective To estimate the resource use of patients with obstructive hypertrophic cardiomyopathy (HCM), stratified by New York Heart Association (NYHA) class, in the English and Northern Irish healthcare systems via expert elicitation.Design Modified Delphi framework methodology.Setting UK HCM secondary care centres (n=24).Participants Cardiologists who actively treated patients with HCM were eligible, of whom 10 from English and Northern Irish centres participated. Recruitment of participants to the study was limited to one expert per site.Methods Responses were collected by electronic quantitative survey. Following the discussion of survey results in a virtual panel, aggregated responses from a final survey were analysed and stratified by NYHA class. Data were analysed without (base case) and with (scenario) interventional cardiologists who conduct septal reduction therapies (SRTs).Results Based on expert opinion, as NYHA class increased, so did the mean±95% CI number of primary care consultations (classes I–IV: 0.64±0.35; 1.07±0.33; 3.29±1.02; 6.00±2.46, respectively) per patient per annum. This was also observed across all types of secondary care consultations, such as mean±95% CI number of cardiovascular-related outpatient visits (classes I–IV: 0.69±0.26; 0.88±0.24; 2.13±0.78; 3.25±1.42, respectively) and inpatient admissions (classes I–IV: 0.01±0.01; 0.04±0.07; 0.94±0.39; 1.90±0.65, respectively) per annum. Patients in NYHA class III were most likely to undergo SRT in their lifetime (mean±95% CI proportion of patients:17.25%±7.19% or 26.30%±13.61% including interventionalists). Across NYHA, experts estimated that septal myectomy was more costly than alcohol septal ablation (mean±95% CI: £15 675±£10 556 vs £6750±£5900, respectively). Prescription of beta-blockers was higher than calcium channel blockers, irrespective of NYHA class.Conclusions Treatment of obstructive HCM is associated with a substantial clinical and economic burden in England and Northern Ireland; the burden of the disease increasing with NYHA class is driven by the need for intensive disease management, hospitalisations and the potential burden of undertaking SRTs.